Interactive Islamic Education: Exploration of Quizizz Based Learning on Student Motivation and Learning Achievement - Mahfudi, Zulfia Nur; Shohib, Muhammad Wildan (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the effect of using Quizizz as a technology-based learning tool on student motivation and academic achievement, specifically in the context of Islamic education. The method used is a literature review with a qualitative-inductive approach, through analysis of various relevant sources to understand how Quizizz can improve student learning outcomes and engagement. The research process includes data reduction, presentation in short narratives, and drawing conclusions. The study results indicate that gamification features such as leaderboards, prizes, and real-time feedback in Quizizz can create a competitive, interactive, and enjoyable learning environment, thereby increasing student motivation. In the context of Islamic education, Quizizz allows for the creative and easy-to-understand delivery of materials such as hadith, fiqh, and Quran memorization. Furthermore, the learning outcome analysis feature helps teachers adjust teaching methods based on student performance data. Overall, the use of Quizizz supports Islamic education in realizing holistic learning goals, both academically and spiritually, and addresses the challenges of education in the digital age. However, this study also highlights the need for solutions to barriers such as technology dependence and limited internet connections to optimize implementation.